Effect of one session of static stretch of shoulder muscles on the performance of throwing in wheelchair athletes of throwing discus, shot put, and javelin sport - Moslehedin, A. H.; Noureddin, K.; Yahya, S.; Hamid, A.; Samaneh, H. (Physical Treatments-Specific Physical Therapy Journal, 2017)
Purpose: In recent years, many people show interest to Paralympics competition because it is dedicated to athletes with disabilities. In order to affect the throwing, static stretching can be applied on the two muscles, i.e. pectoralis major and latissimus dorsi that play an important role in the arm acceleration phase. Normally, before sport activities, static stretching is applied. Stretching increases the flexibility that is effective in the throwing. The important point is the effect of this type of stretching on the throwing function, which is a combination of muscular strength, range of motion and productive torque. This study is going to examine this issue. Methods: In this study, 45 disabled male athletes (15 discus throwers, 15 shot put throwers, and 15 javelin throwers) participated. Before stretching, each athlete did 3 throws, then a static stretching session consisting of 5 sets of 30 seconds stretching followed by 30 seconds of rest between each set, was performed. One minute after the stretching, the athletes did throwing 3 more times. Stretch was of the static type applied on the pectoralis major and latissimus dorsi muscles. Results: Based on study results, no significant change was observed in the amount of throw before and after the stretching (Discus: P=0.47, Shot put: P=0.46, Javelin: P=0.14). Conclusion: Considering data analysis, one session of static stretching of pectoralis major and latissimus dorsi muscles does not create a significant change in the magnitude of throw in disabled athletes engaged in discus, shot put, and javelin throw.